Fractal Fragments: Reflections on Human and More-than-human Matter(s) in the Kogelberg Biosphere, South Africa - Mathilda Slabbert (European Journal of Life Writing)
This critical ecoauto/biographical essay reflects on history, lived experience, personal and public perspectives of socio-environmental issues in the Kogelberg Biosphere, South Africa. The essay combines written and visual texts, varied in form and format, to present a situated reflection on human and more-than-human encounters and biosphere politics. In particular, the essay experiments with travel writing forms, blending academic and creative practice, and evolves into a perambulating journey through a local zone of the biosphere, inviting relational reflection on the planetary crisis.